Sustainable development goals: Recognition of Pancasila education materials in shaping student ethics in the digital era - Sartika, Rika; Praja, Wina Nurhayati; Azis, Abdul (Universitas Negeri Yogyakarta, 2022)
Students' interest in learning and teaching Pancasila Education has not yet thoroughly imbued awareness and sincerity. Students prefer to discuss the actualization and practice of the Pancasila precepts. The method used in this research is a qualitative approach with descriptive analysis and observation methods. Researchers conducted observations, interviews, and distributed google forms to find and dig the required information from students and several related lecturers. Looking at some of the responses and the obstacles felt by students in studying the philosophical and historical Pancasila, the researcher considers it essential to reconstruct the content of the Pancasila Education material in the face of the Industrial Revolution 4.0. The position and role of Pancasila ideology in the scope of Pancasila education must be strengthened and reconstructed more dynamically according to the times. The results obtained from this study show that Pancasila education materials need to be improved and adapted to the developments and guidelines of the digital era, not only centered on theories and concepts but materials are made more exciting and creative so that Pancasila ideology can survive and develop following the goals of the Sustainable Development Goals. (SDGs). So that the character, personality, and ethics of students needed in the 21st Century are fulfilled and optimized for various aspects of life.